Biological control potential of an aphidophagous syrphid, Episyrphus balteatus, De-Geer (Diptera : Syrphidae) on mustard aphid, Lipaphis erysimi (Kalt.) (Homoptera : Aphididae) on cabbage ecosystem in Manipur. - Romabai devi, Y; Kalita, J; Singh, T K (Journal of Experimental Sciences, 2012)
The role of the predator syrphid, Episyrphus balteatus in regulating the field population of the mustard aphid, Lipaphis erysimi (Kalt.) was studied for two subsequent crop-seasons during 2008 – 2010 on cabbage, Brassica oleracea var. capitata. The numerical density of the predator was recorded to increase in response to density of the aphid prey in the field. The correlation analysis showed significant positive correlationship between the predator and prey species i.e. L. erysimi, whereas temperature, relative humidity, rainfall and wind speed correlated negatively with the aphid density in the ecosystem.